2013
DOI: 10.1037/a0032951
|View full text |Cite
|
Sign up to set email alerts
|

Center-based child care and cognitive skills development: Importance of timing and household resources.

Abstract: Growing evidence has linked center-based early care and education settings to improvements in children's cognitive skills. Additional research is needed to more carefully delineate when and for whom these associations are most pronounced. Using data from the Early Childhood Longitudinal Study, Birth Cohort (N <= 6,350;Flanagan & West, 2004), this study examined whether the beneficial effects of center-based care settings for children's cognitive skills at age 5 differ by the age at which children experience t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 77 publications
3
56
0
Order By: Relevance
“…Parent, family, and child characteristics. Several parent, family, and child characteristics were incorporated as covariates because of their connections in prior research with both EEC use and children's school readiness skills Miller et al, 2014;Votruba-Drzal et al, 2013). Time-varying covariates were drawn from Waves 1 and 2 to provide temporal precedence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parent, family, and child characteristics. Several parent, family, and child characteristics were incorporated as covariates because of their connections in prior research with both EEC use and children's school readiness skills Miller et al, 2014;Votruba-Drzal et al, 2013). Time-varying covariates were drawn from Waves 1 and 2 to provide temporal precedence.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Koury and Votruba-Drzal (2014) have shown that there are differences in several aspects of children's home environments related to parental region of origin, including the provision of cognitive stimulation and emotional support. Based on prior research that shows that center-based EEC is associated with the greatest cognitive skills gains among children from less advantaged home environments (Bradley, McKelvey, & Whiteside-Mansell, 2011;Magnuson et al, 2004;Votruba-Drzal et al, 2013), we hypothesize that there may be variability in the implications of center-based EEC experiences based on parental region of origin.…”
Section: Heterogeneity Among Children Of Immigrantsmentioning
confidence: 98%
“…Program continuity supports stability of child care arrangements which is associated with more positive child outcomes (Howes & Hamilton, 1992;Loeb, Fuller, Kagan, & Carrol, 2004). Although quality varies within all types of care (NICHD Early Child Care Research Network, 2002), center care has been found to be associated with positive cognitive outcomes for children, especially those from low-income households (NICHD Early Child Care Research Network, 2002;Votruba-Drzal, Coley, Koury, & Miller, 2013). Few studies have examined the relationship between subsidy policy generosity and program outcomes (Michalopoulos, 2010;Michalopoulos, Lundquist, & Castells, 2010;Schexnayder & Schroeder, 2008;Witte & Queralt, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…The longitudinal analysis of amount of time spent in non-maternal childcare showed inconsistent findings; some suggested significant association with child cognitive outcomes [13], some others did not [2,5,6,9]. Significant associations were found when types of childcare were examined separately.…”
Section: Patterns Of Childcare and Cognitive Developmentmentioning
confidence: 93%